Effectiveness, Attractiveness, and Emotional Response to Voice Pitch and Hand Gestures in Public Speaking - Rodero, Emma (Frontiers in Communication, 2022)
Some nonverbal cues, such as voice pitch and gestures, can influence the individual’s emotional response to different messages. For this reason, Scott (1820), in an old document titled Elocution, defined nonverbal communication as the language of emotion, while the content is the language of ideas. But the research question here is what voice pitch and hand gestures strategies are more effective, attractive, and elicit a stronger emotional response. To answer this question, this study analyzes some pitch and hand gesture strategies in public discourses. In the experiment, 120 participants were exposed to different public presentations with three conditions for voice pitch (few, medium, and many variations) and three for hand gestures (smooth, medium, and strong intensity). Then they rated the effectiveness and attractiveness levels and self-report arousal and valence while their emotional response was registered. Physiological arousal was measured with electrodermal activity (EDA) and valence with Facial Expression Recognition. Participants perceived the medium pitch variations and the medium intensity of gestures as the most effective and attractive strategies with the highest self-reported arousal and valence. The combination that elicited the strongest autonomic arousal was medium pitch variations-strong gestures. Finally, the most positive emotional valence was for many pitch variations and medium gestures and the happiest for the combination many-strong.